2014
DOI: 10.1128/aem.03129-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation and Phylogeny of Anaplasma spp. in Mediterranean Ruminants Reveal the Presence of Neutrophil-Tropic Strains Closely Related to A. platys

Abstract: Few data are available on the prevalence and molecular typing of species belonging to the genus Anaplasma in Mediterranean ruminants. In this study, PCR analysis and sequencing of both 16S rRNA and groEL genes were combined to investigate the presence, prevalence, and molecular traits of Anaplasma spp. in ruminants sampled on the Island of Sardinia, chosen as a subtropical representative area. The results demonstrate a high prevalence of Anaplasma spp. in ruminants, with animals infected by at least four of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 29 publications
4
71
2
3
Order By: Relevance
“…Overall, 66 out of 226 camels (29.2%) were seropositive. The discrepancy between molecular and serological tests could be explained by cross-reactivity of the antigen used in serology with anti-cytoplasmic antibodies, as well as with other autoimmune antibodies and/or with antibodies related to other Anaplasma species closely related to those of A. phagocytophilum [17,18,45]. Notably, previous studies reported a great degree of cross-reactivity in serological tests between Anaplasma species [46][47][48].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Overall, 66 out of 226 camels (29.2%) were seropositive. The discrepancy between molecular and serological tests could be explained by cross-reactivity of the antigen used in serology with anti-cytoplasmic antibodies, as well as with other autoimmune antibodies and/or with antibodies related to other Anaplasma species closely related to those of A. phagocytophilum [17,18,45]. Notably, previous studies reported a great degree of cross-reactivity in serological tests between Anaplasma species [46][47][48].…”
Section: Discussionmentioning
confidence: 96%
“…In particular, all Anaplasma sp. Tunisian strains were closely related to A. platys strains isolated from Chinese goats and to Italian strains isolated from goats and cattle [10,17].…”
Section: A M (Lushi)mentioning
confidence: 99%
See 2 more Smart Citations
“…A. centrale est décrite chez des bovins en Sicile et chez des chevrettes en Espagne (Ceci et al 2014), alors qu'A. bovis est rapportée en Italie et en Espagne (Ceci et al 2014 ;Zobba et al 2014). …”
Section: En Corseunclassified